The death and life of Australian suburbs: Relationships between social activity and the physical qualities of Australian suburban neighbourhood centres. (March 2022) - Farahani, Leila Mahmoudi; Izadpanahi, Parisa; Tucker, Richard
Abstract: This paper reports on research into social activity in commercial/retail centres in Australian low-density suburbs. While low-density suburbs have been criticised for declining vitality and sociability, some commercial/retail precincts still thrive there. This study sought to determine the relationship between the physical qualities of the built environment and social activity in such thriving suburban neighbourhood centres. Three areas in Geelong, Victoria, were studied as representative of three common forms of Australian suburban commercial/retail centre. First, behavioural observations identified which of the three centres was the most vital and sociable. Next, semi-structured interviews with users of that centre who resided in its containing suburb explored perceptions of the environment to identify the physical features that contributed to its social affordances. The findings suggest that diversity of uses is key to the vibrancy of commercial centres. Walkability, perceptions of safety and physical qualities such as landscaping, good pedestrian pathways and pavement dining were also found to contribute to vitality. Importantly, it appears that in neighbourhoods with high transient populations, residents do not associate these types of socially active environments with sense of community. Highlights: This study focuses on identifying the physical features that contributes to the social affordances of commercial streets. The findings suggest that diversity of uses is key to commercial streets' vibrancy. Walkability, perceptions of safety and physical qualities were also found to contribute to vitality of commercial streets.